(untitled) (Archives of Pediatrics of Uruguay, 2025)
Introduction: in 2008, a country in the Southern Cone of Latin America implemented universal childhood vaccination with the 7-valent pneumococcal conjugate vaccine (PCV), later replaced by PCV13 in 2010. Vaccine coverage was over 92%. Since 2004, the pneumococcal polysaccharide vaccine (PPSV23) has been recommended for at-risk adults, and since 2015, PCV13 plus PPSV23 for those at very high risk. Objectives: assess the impact of the universal vaccination strategy on hospitalizations due to invasive pneumococcal disease (IPD) in children and adults in a private general hospital. Methodology: a descriptive and retrospective study conducted in a private tertiary general hospital. It included children and adults hospitalized with a diagnosis of IPD during the period 1/1/2006 to 31/12/232023. Three study periods were established: prior to PCV implementation (2006 to 2007), early post-implementation (2009 to 2015), and late post-implementation (2016 to 2023). Hospitalization rates, disease type, proportion of vaccine and non-vaccine pneumococcal serotypes, and case-fatality and mortality rates were calculated and compared. Categorical variables were described as numbers and percentages. Continuous variables were described as median and range. It was approved by the institutional ethics committee. The degree of univariate association was examined using the Mid-P exact test, Student’s t-test, and Chi-square test, as appropriate. A p-value <0.05 was considered statistically significant. Results: between 2006 and 2023, a total of 129 cases of IPD were hospitalized, 37 in children (mean age 5 years, range 2 to 13 years) and 92 in adults (mean age 68 years, range 15-90 years). The rate/10,000 discharges in children in the 2006-2007 period was 50 (25-75); in the 2009-2015 period: 8.5 (3-14) and decreased to 6.2 (2-10) in the 2016-2023 period (p<0.0003); the reduction percentages were: 82.5% and 87.6% (p<0.00000). In adults, the rate in the 2006-2007 period was 17 (10-25), in the 2009-2015 period it was 6.6 (4.4-9), and 5.3 (3.3-7.3) in the 2016-2023 period; the reduction percentages were 63.5% and 69% (p=0.00002). Pneumonia was the most frequent disease in children 67.5%, followed by bacteremia 21.6%. In adults, pneumonia 77% followed by meningitis 7%. One unvaccinated child died in 2008. Eight adults died, 3 in the 2006-2007 period, 2 in 2009-20215, and 3 in 2016-2023. The case-fatality rate in adults was 9% (8/92). A significant reduction in the mortality rate was observed (p = 0.009). 24 serotypes were identified in adults, showing a significant decrease in the serotypes included in PCV13 from 77% in 2006-2007 to 34% in 2016-2022, (p<0.0000). In children, 16 serotypes were identified, with a 94% decrease in the pre-PCV period to 50% in the post-PCV 2016-2022 period, (p<0.0000). An increase in non-vaccine strains was observed in (2009-2022) 35/62 isolated strains (56%) vs (2006-2007) 6/38 (16%) (p<0.0000). Serotypes 12F, 8, 22F, and 9N were the most frequent. Conclusions: a significant reduction in hospitalization rates for PCV13 vaccine serotypes in the pediatric and adult population, and in mortality, probably due to the herd effect, was observed. An increase in non-vaccine serotypes was also observed.